A6.40 Copy number increase of TLR7 and TLR8 genes in men with rheumatoid arthritis. (13th February 2015) - Martin, GV; Kanaan, SB; Azzouz, DF; Balandraud, N; Picard, C; Auger, I; Arnoux, F; Martin, M; Roudier, J; Lambert, NC
Abstract : Background and objectives: Men are less often affected by Rheumatoid arthritis (RA) than women. In mice studies, it was shown that a duplication in Toll-like receptor 7 (Tlr7) gene is sufficient to potentiate autoimmunity in males. We therefore propose to investigate whether an increase in copy number (CN) of TLR7, and its neighbouring paralog TLR8 on X chromosome, could contribute to the pathogenesis of RA in men. Materials and methods: In a pilot analysis, we had first tested our hypothesis by real-time quantitative PCR assay to assess CN of TLR7 gene and TLR8 compared to Beta-Globin gene (HBB), using the relative standard curve calculation method, on DNA from PBMCs of 49 men with RA and 42 healthy controls. TLR7/8 copy numbers significantly increased in PBMCs from men with RA when compared to healthy men. Nevertheless, because men with RA were significantly older than healthy donors, the increased TLR7/8 CN could be age-dependent. In the current study, we have tested whether TLR7/8 CN varies with age on a large number of controls from birth to 82 years old (160 men and 180 women). We also tested an additional autosomal RPP30 gene to further validate our results. DNA samples from peripheral blood of 49 men with RA versus 160 healthy men and 44 women with RA versus 180 healthy women were tested for TLR7/8 CN compared to mean CN values of HBB and RPP30. Similarly, DNA samples from PBMCs of 53 men with RA versus 42 healthy men and 40 women with RA versus 41 healthy women were analysed. Results: TLR7 or TLR8 CN does not vary with age in healthy individuals (women or men). Similar findings were observed in patients with RA. Nevertheless, we confirmed that men with RA had an increased TLR7 and TLR8 CN in peripheral blood compared to healthy men (p < 0.0001 and p = 0.002 respectively). A rather opposite trend was observed in women with RA. Similar results were observed in PBMCs. Conclusions: We have presented evidence that copy number of X-linked TLR7 and TLR8 genes increases in men with RA. This increase is not only disease dependent but also sex-dependent. We are currently validating our results by digital droplet polymerase chain reaction to confirm this genetic heterogeneity between men and women with RA.